Overuse of β₂-Agonist Medications in Patients with Asthma: A Literature Review - Daffa Agustian Pujianto; Dara Anggieta Octaryani; Regina Fauziah; Kayisa Issyakirawahyu; Zahra Aqiqah; Alifa Syifa Fauziah; Heri Ridwan (AACENDIKIA: Journal of Nursing, 2025)
Asthma is a chronic inflammatory disease of the airways characterized by reversible bronchial obstruction and airway hyperresponsiveness. β₂-agonists, especially short-acting β₂-agonists (SABA), act as quick-relief medications because they do not address the underlying inflammation of asthma. However, excessive use of β₂-agonists increases the risk of severe exacerbations, reduced asthma control, and increased mortality. This study aims to review the characteristics of β₂-agonists and the phenomenon of overuse in asthma patients. A literature review was conducted by searching articles in the Google Scholar, ScienceDirect, and PubMed databases using the keywords “asthma,” “β₂-agonist,” “Short-acting β₂-agonists (SABA),” and “overuse,” covering the period from 2015 to 2025. Selection was performed using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) method, through a process of screening titles, abstracts, and full-text based on inclusion criteria. SABA overuse was defined as the use of ≥3 canisters per year or exceeding the reasonable limit of reliever use for symptom control. Several countries reported high prevalence of overuse, namely 15.9% in Taiwan, 30% in Sweden, 36–38% in Germany, and 44.8% in Canada. Excessive use of β₂-agonists is associated with an increase in recurrent exacerbations, the need for oral corticosteroids, decreased lung function, and an increased risk of mortality. Therefore, controlling inflammation through the use of inhaled corticosteroids (ICS) remains the mainstay of asthma therapy to prevent complications and reduce dependence on SABA.